IDENTIFIKASI KERUSAKAN BANGUNAN GEDUNG SEKOLAH DASAR DI KOTA PONTIANAK BERDASARKAN FAKTOR PERUSAK KAYU - niel, Da; Diba, Farah; Husni, Harnani (Universitas Tanjungpura, 2014)
This research aims to study and identify the extent of damage to buildings in Pontianak City Elementary School caused by destructive factors of the building, studying and identifying the types of organisms that destroy wood and look for a solution in accordance with the method of building maintenance. The study was conducted in 3 elementary school in each the district, namely Pontianak Kota, Pontianak Timur, Pontianak Barat, Pontianak Utara, Pontianak Selatan, and Pontianak Tenggara. Total sample was 18 elementary school. The research method used forensic engineering. The results showed that the level of damage occurs due to the lack of maintenance of buildings and errors in the use of construction materials. Large part of damage in Elementary School building was caused due to the lack maintenance of the building and by the use of raw materials that do not comply with the standard. The damaged in building mostly by wood destroying organisms such as termites, fungi, insect borers, and other insect pests. Treatments and maintenance of building schoolÂ in the city of Pontianak is the determinant of the development activities and the prevention of damage to the building which will reduce the level of damage. The wood destroying organism need to control to prevent the huge damage. Maintenance of building is important, especially in the parts of construction of components which is susceptible to damage by wood organism . Keywords : Forensic engineering, wood destroying organism, Elementary School building, termites, fungi